IDENTIFIKASI FAKTOR–FAKTOR UTAMA PENYEBAB TERJADINYA KETERLAMBATAN WAKTU PENYELESAIAN PADA PEKERJAAN INFRASTRUKTUR GEDUNG DI BANDA ACEH - Darmawi Darmawi; Muttaqin Muttaqin; Anita Rauzana (Prodi Magister Teknik Sipil Unsyiah, 2020)
The implementation of building construction projects in the city of Banda Aceh in the Fiscal Year 2015 to 2017, many experienced delays in the implementation caused by many factors both internal factors and external factors. This research was conducted with the aim to find out the top five rankings of the main factors that caused the delay in the implementation of building construction project in Banda Aceh City and to get the main factors that can be done to prevent/overcome delays in the implementation of building construction projects in Banda Aceh City. Data collection was conducted by questionnaire survey method to 40 respondents from the owner and 40 respondents from the contractor who had been involved in handling building construction projects. Based on the results of data analysis and discussions that have been carried out, it is determined that the top five ranks of the main factors causing the delays in implementation of the building construction project in the city of Banda Aceh are: Design changes/work details at the time of implementation, natural disasters such as fires, flood, bad weather, storm/hurricane, earthquake, landslide; Conditions and environment that are not as expected; Wrong/incomplete in making planning (drawings/specifications); and Often/ lot of work is added/less. While the top five ranking solutions for the main factors that can be done to prevent/overcome delays in implementation of building construction projects in Banda Aceh City are: Reviewing the design before starting work; Knowing weather prediction during implementation; Conducting feasibility studies and field investigations before the execution of work; During the Pre Construction Meeting the contractor must clarily all documents to be clear, and Minimize the occurrence of added/less work.